Evaluación de la ergonomía en los estudiantes de clínica I y V de la Universidad de las Américas - Arévalo Carrillo, Katerine Lizbeth (2018)
This study is carried out with the purpose of evaluating the type of ergonomics that the students who are crossing clinic I and clinic V have in the Dental Clinic of the UDLA. The specific objectives of the study are: to compare the ergonomics of clinical students I and V of the University of the Americas. Determine the most common positions of students. The method of data collection was based on a survey called the MAPETO-CL survey this survey was completed by me through the review of photographs that were taken to the students at the time they were working with their patients. The results showed that 20% of all students occupied all the back of the dental seat and 30% of the students had both feet on the floor, and 67% of the students had a distance of 30 to 40 cm from their eyes to the mouth of the patient. In conclusion, clinical students I have better ergonomics at the time of attending to the patient than students of clinic V. It is recommended that students consider the position they acquire at the time of care with the patient to avoid future muscle problems. - skeletal and have a healthy life.